Causes Of Pastoralists And Farmers’ Conflict In Benue State Nigeria And Integrating Nomadic Education For Managing It - Agbegbedia, Anthony; Awe, Norah Ene (PT ARRUS Intelektual Indonesia, 2025)
Pastoralists and farmers’ conflicts have persisted for too long in Nigeria and particularly in Benue State, and the respective mechanisms adopted for managing it have brought little or no progress in dousing it. The paper thus explored the causes of the conflict in the state as well as the need for integrating nomadic education for managing it. Primary and secondary sources were used for gathering data. The paper adopted the environmental scarcity theory and utilised the survey and descriptive research design. The survey method was used to elicit quantitative data from 480 respondents aged 10years and above from purposively sampled communities across the 3 senatorial regions in the state while Key Informant Interviews and Focus Group Discussion with purposively sampled farmers, pastoralists, community and Fulani leaders were relied upon to generate the qualitative data for the study. Findings revealed that crop damages and activities of young pastoralists are the major causes of this conflict. Other causes include bush burning, unemployment, drought and water scarcity amongst others. Furthermore, respondents were of the view that introduction of nomadic education scheme will help in reducing the conflict. The paper concluded that pastoralists-farmers conflict is destructive and has dare impacts on the state in particular and the country (Nigeria) in general. Nomadic education should be incorporated into the mainstream activities of managing farmers and pastoralists conflict.